Chemical composition and biological potential of Thymus Willdenowii Boiss. & Reut. essential oil. Issue 5 (4th March 2021) - Zeghib, Assia; Calliste, Claude-Alain; Simon, Alain; Charfeddine, Rim; Aouni, Mahjoub; Duroux, Jean-Luc; Kabouche, Ahmed; Kabouche, Zahia
Abstract: The fresh aerial parts of Thymus willdenowii Boiss. & Reut. (syn. Thymus hirtus Willd.) were hydrodistilled in a Clevenger type apparatus and analyzed by GC and GC-MS. 44 Components were identified representing 97.3%, with 1, 8-cineole (34.62%), camphor (18.55%), α-pinene (9.46%) and camphene (5.38%) as the main components. T. willdenowii essential oil was not cytotoxic (CC50 = 97.65 µg/mL) towards Vero non-tumoural cells, exhibiting good antibacterial and antiproliferative (30.8 ± 3.1% inhibition) potentials against four tested pathogenic bacteria and Human colorectal cell line HT-29, respectively. The essential oil did not show a DPPH radical scavenging activity, by Electron Spin Resonance spectroscopy (ESR), and it lacks antiviral effect towards coxsackievirus B3. Graphical Abstract: